FAKTOR-FAKTOR YANG MEMPENGARUHI COST OF DEBT DAN COST OF EQUITY DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL MODERATING - Zahra Dinul Khaq; Zulaikha Zulaikha; Fuad Fuad (Jurnal Akuntansi dan Pajak, 2022)
This study aims to examine empirically the effect of tax avoidance and corporate social responsibility disclosure against cost of debt and cost of equity with institutional ownership as a moderating variable. The reason for this research is one of them because of the inconsistency of some previous research results so that need to be tested again. The study population included all manufacturing companies listed on the Indonesian Stock Exchange (IDX) during the observation period of 2014-2016. Data sources are secondary data obtained through intermediate media in the form of documents. The data used in the form of Composite Stock Price Index (IHSG), sustainability report company, and company annual report obtained from library IDX. The sample used in this research is extracted by using purposive sampling method. After deducting some criteria, 42 companies were determined as samples. Analytical technique in this research use multiple linear regression analysis with the help of software Eviews ver 9. Test results show that tax avoidance has a positive effect on cost of debt and cost of equity. Tax avoidance poses risks, increasing the cost of debt and cost of equity. Institutional ownership has proven to weaken the influence of tax avoidance on cost of debt, but it is not proven to moderate the effect of tax avoidance on cost of equity. The results of this study also indicate that corporate social responsibility disclosure negatively affect cost of debt and cost of equity. The higher the disclosure of corporate social responsibility the lower the risk of the company, thereby reducing cost of debt and cost of equity. Institutional ownership has been shown to strengthen the impact of corporate social responsibility disclosure on cost of debt and cost of equity. Keywords : tax avoidance, corporate social responsibility disclosure, cost of debt, cost of equity, institutional ownership.